A CHAOTIC SYNCHRONIZATION OF DOUBLE CONVECTION - Bulut, G. Gunay; Guler, Hasan (Ieee, 2018)
The concept of chaos is used to describe irregularity and disordianance situations in daily life, as well as to describe the complex behavior of nonlinear systems in engineering. The complex behavior of chaotic systems used in many applications, especially in the field of secure communications, in fact has a harmony on itself that can not be easily enucleated.. Chaos control and chaotic synchronization are both needed for effective usage of chaotic systems which are frequently used in the engineering field. In this study, master slave synchronization of Rucklidge chaotic system which is available in the literature aldready and is less scrutinised than other chaotic systems, has been achived with active controller. Modeling of the Rucklidge chaotic system and simulation outputs of master-slave synchronization have been accomplished through the LabVIEW program. When the theoretical information is compared with the simulation results, it is observed that the master-slave synchronization has been performed.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Chaos; Rucklidge Chaotic System; Master Slave Synchronization; Active Control; LabVIEW; Simulation